Time-series transcriptome provides insights into the gene regulation network involved in the icariin-flavonoid metabolism during the leaf development of Epimedium pubescens - Xu, Chaoqun; Liu, Xiang; Shen, Guoan; Fan, Xuelan; Zhang, Yue; Sun, Chao; Suo, Fengmei; Guo, Baolin (Frontiers in Plant Science, 2023)
Herba Epimedii (Epimedium) leaves are rich in prenylated flavonol glycosides (PFGs) with high medicinal value. However, the dynamics and regulatory network of PFGs biosynthesis remain largely unclear. Here, we combined metabolite profiling (targeted to PFGs) and a high-temporal-resolution transcriptome to elucidate PFGs regulatory network in Epimedium pubescens, and identified key candidate structural genes and transcription factors (TFs) involved in PFGs accumulation. Chemical profiles analysis revealed that PFGs content was quite different between buds and leaves and displayed a continuous decline with leaf development. The structural genes are the determinant reasons and they are strictly regulated by TFs under temporal cues. We further constructed seven Time-Ordered Gene Co-expression Networks (TO-GCNs) of PFGs biosynthesis genes (including EpPAL2, EpC4H, EpCHS2, EpCHI2, EpF3H, EpFLS3 and EpPT8) and three flavonol biosynthesis routines were then predicted. The TFs involved in TO-GCNs were further confirmed by WGCNA analysis. 14 hub genes, including 5 MYBs, 1 bHLH, 1 WD40, 2 bZIPs, 1 BES1, 1 C2H2, 1 Trihelix, 1 HD-ZIP and 1 GATA were identified as candidate key TFs. The results were further validated by TFs binding sites (TFBS) analysis and qRT-PCR. Overall, these findings provide valuable information for understanding the molecular regulatory mechanism of PFGs biosynthesis, enriching the gene resources, which will guide further research on PFGs accumulation in Epimedium.